Oral Cavity Beta-Defensin Levels Are Regulated Differently during Radiotherapy in Head and Neck Cancer Patients - Keskin Mutlu; Suomi Emma; Harmankaya İlknur; Karaçetin Didem; Sorsa Timo; Gürsoy Ulvi Kahraman (MDPI, 2025)
Background: Human beta-defensins (hBDs) are small cationic peptides of the epithelium with broad antimicrobial and immune response-regulatory activities. hBDs are also related to oncogenesis, and their secretion profiles are affected by radiotherapy treatment. The present study aimed to investigate the oral cavity hBD 1-3 levels in head and neck cancer patients and its relation to radiotherapy treatment. Methods: Sixteen head and neck cancer patients (all with a history of smoking) were included in this study. Periodontal parameters were measured before radiotherapy, and medical information was collected from registries. Oral rinses of the patients were collected before radiotherapy; on the 1st, 3rd, and 6th weeks of radiotherapy; and the 1st month following the end of radiotherapy. hBD 1–3 levels were measured using ELISA. Results: Oral hBD-1 levels increased during radiotherapy at week 6 (p = 0.019). hBD-1 levels returned to pretreatment levels after the end of radiotherapy. No significant change was detected for hBD-2 or hBD-3 levels during or after radiotherapy. Conclusions: The constant expression of hBD-1, which is distinct from the infection and inflammation-dependent expression profiles of hBD-2 and hBD-3, may explain why this peptide is the only one affected by radiotherapy.